2020
DOI: 10.15252/embj.2019103444
|View full text |Cite
|
Sign up to set email alerts
|

Osmostress enhances activating phosphorylation of Hog1 MAP kinase by mono‐phosphorylated Pbs2 MAP 2K

Abstract: The MAP kinase (MAPK) Hog1 is the central regulator of osmoadaptation in yeast. When cells are exposed to high osmolarity, the functionally redundant Sho1 and Sln1 osmosensors, respectively, activate the Ste11‐Pbs2‐Hog1 MAPK cascade and the Ssk2/Ssk22‐Pbs2‐Hog1 MAPK cascade. In a canonical MAPK cascade, a MAPK kinase kinase (MAP3K) activates a MAPK kinase (MAP2K) by phosphorylating two conserved Ser/Thr residues in the activation loop. Here, we report that the MAP3K Ste11 phosphorylates only one activating pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 68 publications
1
34
1
Order By: Relevance
“…In this study, Slt2 was significantly upregulated during the entirety of the methanol induction phase (p-Value < 0.001 and log2 fold changes > 1.48) ( Figure 5A and Supplementary Table S2); the Wsc family sensors (Ohsawa et al, 2017) were also significantly upregulated in this regard (p-Value < 0.05 and log2 fold changes > 0.75) ( Figure 5A and Supplementary Table S2). Although Hog1, a central regulator of osmotic adaptation in yeast, was not significantly upregulated in this study, the Ste11-Pbs2-Hog1 MAPK and Ssk2/Ssk22-Pbs2-Hog1 MAPK cascades (Tatebayashi et al, 2020) have been reported to be activated by osmotic sensors when cells are exposed to high osmotic pressure, suggesting that both Ste11 and Pbs2 are involved in the osmotic stress response (Zarrinpar et al, 2004). The MAPK that replaced Hog1 upregulation in this study was Slt2.…”
Section: The Upregulated Genes Of the Mapk Signal Pathway May Be Invocontrasting
confidence: 56%
“…In this study, Slt2 was significantly upregulated during the entirety of the methanol induction phase (p-Value < 0.001 and log2 fold changes > 1.48) ( Figure 5A and Supplementary Table S2); the Wsc family sensors (Ohsawa et al, 2017) were also significantly upregulated in this regard (p-Value < 0.05 and log2 fold changes > 0.75) ( Figure 5A and Supplementary Table S2). Although Hog1, a central regulator of osmotic adaptation in yeast, was not significantly upregulated in this study, the Ste11-Pbs2-Hog1 MAPK and Ssk2/Ssk22-Pbs2-Hog1 MAPK cascades (Tatebayashi et al, 2020) have been reported to be activated by osmotic sensors when cells are exposed to high osmotic pressure, suggesting that both Ste11 and Pbs2 are involved in the osmotic stress response (Zarrinpar et al, 2004). The MAPK that replaced Hog1 upregulation in this study was Slt2.…”
Section: The Upregulated Genes Of the Mapk Signal Pathway May Be Invocontrasting
confidence: 56%
“…1B, Zone 2b) to 18 MPa and then remained stable until the end of the glycerol ramp, meaning that yeasts consumed less and less glucose as the ramp continued to a point where the glucose consumption ceased. Experimental and modelling studies have demonstrated the importance of key factors as Hog1 and turgor pressure upon moderate hyperosmotic shocks by NaCl from 0.2 to 1.8 M (up to about 5.3 MPa and down to water activity 0.96) (Klipp et al ., 2005; Muzzey et al ., 2009; Parmar et al ., 2011; Petelenz‐Kurdziel et al ., 2013; Tatebayashi et al ., 2020). Here, we show that glucose uptake occurred up to 13.5 MPa (down to 0.906 water activity) meaning that metabolism continued up to this limit.…”
Section: Resultsmentioning
confidence: 99%
“…Ste11 is a MEK kinase involved in the cellular responses to both pheromone and hypoosmolarity (Harris et al, 2001;Nishimura et al, 2016;Tatebayashi et al, 2006;Tatebayashi et al, 2020) (Figure 7A). It was an encouraging validation of our XL-MS methodology to observe direct interaction between the N-terminus of Ssa1 and the unstructured regulatory domain of Ste11, one of the first identified client proteins of Hsp90 (Figure 7B).…”
Section: Ssa1 Is Involved In the Selective Activation Of Ste11-mediated Signalingmentioning
confidence: 99%
“…Although the R305 dimethylation status had minimal impact on the pheromone response, previous studies have demonstrated that some hyper-active mutations within this region (e.g. STE11-Q301P or STE11-DDD) rescue the osmo-adaptation defect caused by deletion of upstream Ste20 kinase upon high osmolarity (Tatebayashi et al, 2006;Tatebayashi et al, 2020). We examined the ability of Ste11 R305 mutants to complement the loss of Ste11 in response to osmotic shock.…”
Section: Ssa1 Is Involved In the Selective Activation Of Ste11-mediated Signalingmentioning
confidence: 99%